FUNGSI PENDAMPINGAN PASTORAL KONSELING BAGI KARYAWAN YANG MENGALAMI STRES KERJA PADAPT.SINAR PRATAMA CEMERLANG DI MANADO - Alvira Rivani Lesawengen; Wolter Weol; Agnes B.J Raintung (LIMMUD: Jurnal Ilmu Keagamaan dan Sosial Humaniora, 2024)
This research aims to explore the importance of mental well-being and work stress management in PT. Pratama Cemerlang Rays. Using a descriptive qualitative approach, this research analyzes working conditions in companies, factors that cause stress, and the role of pastoral counseling in supporting employee welfare. Data was collected through observation and in-depth interviews with employees. Research findings show that work pressure, excessive workload, and interpersonal conflict are the main causes of work stress in companies. Additionally, inadequate company policies in addressing employee mental well-being exacerbate the situation. Pastoral counseling has been proven to be effective in providing emotional and spiritual support, helping employees overcome work stress and increasing productivity. The results of this research show the important role of management in creating a healthy and supportive work environment, as well as integrating a pastoral counseling approach as part of the company's stress management strategy.